Cost-effectiveness of home non-invasive ventilation in patients with persistent hypercapnia after an acute exacerbation of COPD in the UK. Issue 5 (23rd February 2023) - Murphy, Patrick Brian; Brueggenjuergen, Bernd; Reinhold, Thomas; Gu, Qing; Fusfeld, Laura; Criner, Gerard; Goss, Thomas F; Hart, Nicholas
Abstract : Home non-invasive mechanical ventilation (HMV) with home oxygen therapy (HOT) in patients with persistent hypercapnia following an acute exacerbation of chronic obstructive pulmonary disease delays hospital readmission. The economic impact of this treatment is unknown. We evaluated the cost-effectiveness of HMV in the UK healthcare system using data from a previously published efficacy trial. Quality-adjusted life-years (QALYs) were computed from EQ-5D-5L. Accounting for all direct patient costs HOT-HMV was £512 (95%CI £36 to £990) more expensive per patient per year than HOT-alone. This small increase in cost was accompanied by increased quality of life leading to an incremental cost-effectiveness ratio of £10 259 per QALY. HOT-HMV was cost-effective in this clinical population. Trial registration number: NCT00990132 .